Self-compatibility and floral morphology of almond cultivars - Rovira M.; Miarnau X. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Self-compatibility is an important almond trait aimed in new cultivars of most breeding programs. Nevertheless, different levels of self-fertility occur in almond self-compatible cultivars. Some hypotheses have been postulated about this phenomenon, and it seems that different aspects could be involved. One of them is the position of the stigmata in relation to the anthers in the flowers. In this work the morphology of almond flowers has been studied in 27 almond self-compatible genotypes (12 cultivars and 15 advanced selections from IRTA’s almond breeding program). Data have been collected in 100 flowers/genotypes measuring the pistil and higher stamen length. According to these results, flowers were classified as “hypostigmate” (stigmata below the anthers) or “epistigmate” (stigma above the anthers). On the other hand, self-fertility percentages were studied in these self-compatible genotypes for several years, by counting the number of flowers present in bagged branches and the final fruit set obtained. No correlation was found between floral morphology and levels of self-fertility. Other aspects involved in the levels of almond self-fertility, apart from the morphology of the flower, are yet to be evaluated.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)